Extrusion cooking : technologies and applications - Guy, R. C. E. (Robin C. E.) (Woodhead Publishing series in food science and technology., 2001)
Extrusion cooking is an ideal method for manufacturing a number of food products from snacks and breakfast cereals to baby foods. However, as a complex multivariate process it requires careful control if product quality is to be maintained. Edited by a leading authority in the field, and with an international team of contributors, this important collection reviews the key factors affecting quality and how they can be controlled in manufacturing a range of extruded products. The first part of Extrusion Cooking</> looks at general influences on quality. There are chapters on the selection of raw materials, criteria for selecting the right extruder, analysing and optimising thermal performance in extrusion cooking, and effective process control. There is also an important chapter on maintaining nutritional quality in extruded products. The second part of the book looks at the application of extrusion in particular product groups. Each chapter examines the range of extruded products within the product group, the specific production issues and future trends. It also includes chapters on key products such as breakfast cereals, snack foods and baby foods. Extrusion cooking will be widely welcomed as a major reference in maximising the quality of extruded products. A key reference to improving efficeincy and quality on extruded products.